ROLE OF CT SCAN IN THE DIAGNOSIS OF BRAIN INFECTIONS - Imran, Sabina; Idrees, Muhammad (Journal of Ayub Medical College Abbottabad, 2002)
Background: Brain infections are quite common in low socioeconomic class due to poor nutrition and over populated living conditions. The outcome is usually grave unless promptly diagnosed and properly treated. This study was designed to evaluate the role of CT Scan in the early and correct diagnosis of brain infection. Methods: CT Scan brain both pre and post I/V contrast was performed in patients presenting with high grade fever and headache / neurological symptoms as well as ear and sinus problems. Results: 250 consecutive patients with the above mentioned complaints underwent CT Scan brain. 114 patents had positive scans. This comes to about 45.6%. The remaining 136 patients with normal scans included uncomplicated meningitis cases as well as patients with normal cerebro spinal fluid/CSF laboratory reports. Conclusion: The study showed that CT Scan is a useful investigation in the definitive/ final diagnosis of brain infection. Key Words: Brain abscess, Meningitis, Tuberculoma, Encephalitis, Subdural empyema Computerized tomography.